Creating Wildflower Habitats in Golf Course Out-Of-Play Areas - Rebecca Nestle; Grace Cope; Nicole Benda; Adam G. Dale (EDIS, 2021)
Habitat loss from urbanization and agricultural intensification is reducing native bee and monarch butterfly populations, but golf courses in urban areas present an opportunity to mitigate the negative effects of urbanization on pollinators and the environment. It is feasible to enhance a golf course’s ability to support more species and a greater abundance of wildlife by planting the 40% to 70% of acreage not used for the game of golf in wildflowers. With the most golf courses of any US state, Florida is poised to set the stage for golf course environmental stewardship. This 8-page fact sheet written by Rebecca Nestle, Grace Cope, Nicole Benda, and Adam G. Dale and published by the UF/IFAS Entomology and Nematology Department is intended to provide guidelines for Florida golf course superintendents to aid in their efforts to conserve important wildlife while reducing maintenance inputs and associated costs. https://edis.ifas.ufl.edu/in1316